"Bananas are for Women, Coffee is for Men": Gendered Narratives of Agricultural Histories on Mount Meru, Tanzania. (4th March 2022) - Williams, Beth Ann
Abstract: The history of coffee cultivation on Mount Meru in northern Tanzania has been narrated by men and most scholars as a tale of extraordinary achievement and unfortunate decline. Meru women, however, associate coffee agriculture with gender inequality and social disorder. Complicating narratives of cash crop agriculture as a straightforward communal good, Williams uses oral histories to explore alternative renderings of Meru agricultural history, centering memories that highlight coffee's role in reifying patriarchal power. Women's concern with labor exploitation and emphasis on relational integrity challenge our understanding of what coffee represents in Meru history and our ideal models for pursuing sustainable growth through cash crop commodities.